2020
DOI: 10.1029/2020jc016091
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Circulation and Variability Beneath Nioghalvfjerdsbræ (79 North Glacier) Ice Tongue

Abstract: The floating ice tongue of 79 North Glacier, a major outlet glacier of the Northeast Greenland Ice Stream, has thinned by 30% since 1999. Earlier studies have indicated that long‐term warming of Atlantic Intermediate Water (AIW) is likely driving increased basal melt, causing the observed thinning. Still, limited ocean measurements in 79 North Fjord beneath the ice tongue have made it difficult to test this hypothesis. Here we use data from an Ice Tethered Mooring (ITM) deployed in a rift in the ice tongue fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 63 publications
6
37
0
Order By: Relevance
“…Those results are in line with Lindeman et al. (2020), who found evidence for fast changes in T‐S characteristics associated with isopycnal oscillations induced by such waves.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Those results are in line with Lindeman et al. (2020), who found evidence for fast changes in T‐S characteristics associated with isopycnal oscillations induced by such waves.…”
Section: Discussionsupporting
confidence: 92%
“…At that location, Lindeman et al. (2020) observed a major shift in the circulation pattern end of November, simultaneous to the increase in M2 inflow and M1 speeds observed in this study, indicated for example, by the sign change of the PC1 of the intra‐annual variability (see Section 3.3, Figure 5). Schaffer et al.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Warm AIW flows into the ice shelf cavity and induces submarine melting (Schaffer et al., 2020). The maximum AIW temperature below the floating ice tongue that was measured by moored instruments at 500 m depth was 1.5°C in July 2017 (Lindeman et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This type of mooring has, therefore, not been utilized as extensively in Greenland as in Antarctica. Indeed, only four sub-ice-shelf moorings have been deployed in Greenland: one beneath Nioghalvfjerdsrae Ice Shelf in the northeast (Lindeman et al, 2020) and three beneath Petermann Gletscher Ice Shelf (PGIS) in the north (Münchow et al, 2016;Washam et al, 2018Washam et al, , 2019. We here report on ocean time series data from two SBE 37-SM Microcat Conductivity-Temperature (CT) sensors located along one of these mooring lines beneath PGIS within 5 and 25 m of the ice base.…”
Section: Introductionmentioning
confidence: 99%